EVALUASI ESTETIKA LANSKAP JALAN PADA JALAN RAYA SOEKARNO HATTA KOTA MALANG - Mbete Tani, Maximus Seno; Alfian, Rizki; Djoko, Riyanto (Fakultas Pertanian, 2018)
Aesthetic qualities assessment on sidewalks needs to be done to find out people's perceptions and preferences regarding the characteristics of the road landscape environment especially in relation to the use and influence of the curb trees visually. This study aims to study and evaluate the visual aesthetic qualities of trees in the landscape of the road and to study the visual perceptions of canopy and flower form on the trees. The simulation study was conducted on the landscape of Soekarno Hatta Road Malang City, considering the function of the road as a common circulation path and has a clear landuse. This research was conducted by survey method, literature study and simulation. Stages of research activities include: (1) preparation stage, (2) implementation stage and (3) data processing and recommendation stage. At the processing stage carried out the processing and analysis of questionnaire data of respondents who have done using SBE and SD. The identification done on Soekarno Hatta road landscape to the type and number of trees there are several types of vegetation Trembesi (Samaneasaman) with the amount of 50, Mangga (Mangiferaindica) with the amount of 5, Angsana (Pterocarpusinsidus) with the number of 65 and Palem king (Roystonearegia) The analysis of visual quality performed, it is known that the highest value of SBE has an average value between 47.05-87,26, the value of SBE is having average value between 20,76-43,34, low value of SBE has the average value, average between 2.62-19.53. Semantic Differential Analysis conducted, it is known that the highest SD value has a value> 1.7. A high-quality visual landscape represents a landscape that looks cool, beautiful, spacious, organized, and clean. Analysis performed, it is known that the lowest SD value has a value 1,7. Lanskap kualitas visual tinggi menggambarkan lanskap yang terlihat sejuk, indah, luas, tertata, dan bersih. Analisa yang dilakukan, diketahui bahwa nilai SD terendah memiliki nilai < 1,7. Lanskap kualitas visual rendah menggambarkan lanskap yang terlihat gersang, sempit, berantakan, jelek dan kotor.